A semantic framework to support resource discovery in future cloud markets. (26th January 2015) - Modica, Giuseppe Di; Tomarchio, Orazio
The market of cloud resources is currently dominated by proprietary solutions for what concerns resource delivering, pricing models and service level agreements. In the future cloud markets, when cloud standards will get mature and full interoperability among cloud systems will be a reality, the competition challenge among providers will be played on the capability of supplying high and differentiated QoS levels. In this new scenario advanced and flexible mechanisms to support the matchmaking between what providers offer and what customers demand must be devised. Along with an analysis of the current cloud offering in terms of pricing model, SLA negotiation capabilities, service performance levels and cloud application requirements, this work proposes the definition of a semantic model to support the supply–demand matchmaking process in future cloud markets. Leveraging on a semantic description of the cloud resources' features, customers will be able to discover cloud offers that best suit their own business needs. Tests conducted on an implementation prototype proved the viability of the approach.